1986
DOI: 10.1111/j.1399-3054.1986.tb01224.x
|View full text |Cite
|
Sign up to set email alerts
|

Changes in cuticular transpiration rate and cuticular lipids of oat (Avena sativa) seedlings induced by water stress

Abstract: Two cultivars of oat (Avena sativa L. cvs Pendek and Stormogul II) were exposed to short periods of water‐deficit stress on five consecutive days. The plants responded to the stress by decreasing their cuticular transpiration rate. After two stress periods the cuticular transpiration rate was reduced by 30% for Pendek and by 47% for Stormogul II, and after another three stress periods by 30% and 20%, respectively. These reductions were correlated neither to changes in the total amount of what is generally call… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
24
0
1

Year Published

1990
1990
2013
2013

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 38 publications
(28 citation statements)
references
References 11 publications
2
24
0
1
Order By: Relevance
“…This strong correlation is not as obvious in other species. A similar correlation of multiple drying events to wax deposition was originally shown for seedlings from five oat cultivars (Bengtson et al, 1978), although a subsequent study found no significant correlation for two of the cultivars (Svenningsson and Liljenberg, 1986). No relationship was found between epidermal conductance and wax load in barley (Hordeum vulgare) cultivars that were subjected to dehydration stress (Larsson and Svenningsson, 1986).…”
Section: Discussionmentioning
confidence: 55%
“…This strong correlation is not as obvious in other species. A similar correlation of multiple drying events to wax deposition was originally shown for seedlings from five oat cultivars (Bengtson et al, 1978), although a subsequent study found no significant correlation for two of the cultivars (Svenningsson and Liljenberg, 1986). No relationship was found between epidermal conductance and wax load in barley (Hordeum vulgare) cultivars that were subjected to dehydration stress (Larsson and Svenningsson, 1986).…”
Section: Discussionmentioning
confidence: 55%
“…Amounts and compositions of soluble cuticular lipids vary widely among species (Baker 1982); they also change during leaf developAbbreviation: CM = cuticular membranes ment (Whitecross and Armstrong 1972;Baker 1974;Haas 1977;Bukovac et al 1979;Freeman et al 1979;Baker and Hunt 1981;Baker 1982). A relationship between the amounts and-or composition of cuticular waxes and the permeability of the cuticle to water or solutes has been observed repeatedly (Possingham et al 1967;Bengtson et al 1978;Bukovac et al 1979;O'Toole et al 1979;Baker and Hunt 1981 ;Hunt and Baker 1982;Svenningsson and Liljenberg 1986;Larsson and Svenningsson 1986).…”
Section: Introductionmentioning
confidence: 97%
“…Leaf width at the middle of the leaf length (Width) was also calculated for five leaves from each of six individuals per species with the Digital Image Analysis System (Delta-T, United Kingdom). Cuticular transpiration rates (mg H 2 O · m −2 · min −1 , TRc) were measured on detached leaves after natural desiccation caused stomatal closure (Svenningsson and Liljenberg 1986). TRc for each species were determined gravimetrically from one large leaf from each of six individuals-generally the second youngest fully expanded leaf.…”
Section: Methodsmentioning
confidence: 99%
“…A drought tolerance strategy would correspond to low rates of water loss to nonphotosynthetically related processes, such as cuticular transpiration (Svenningsson and Liljenberg 1986), as well as lower relative water content at turgor loss point, reflecting capacity to maintain turgor under drought stress conditions (Hinckley et al 1983). Drought-tolerant species often show higher resistance to hydraulic flow through roots than drought avoiders and escapers (Lo Gullo and Salleo 1988;Lo Gullo et al 1998), as well as lower stomatal conductance in well watered conditions ( Filella et al 1998;Gratani and Varone 2004;Gulias et al 2002;Lo Gullo and Salleo 1988).…”
Section: Introductionmentioning
confidence: 99%